The SS in heavy metal lyrics. (1st September 2020) - Pieper, Henning
The article seeks to examine why heavy metal bands used history and imagery associated with the 'Schutzstaffel' (SS). This includes the reasons for the focus on this particular organization as well as the intentions behind it: are compositions about historical facts or rather fictitious topics, that is, are they an accurate analysis, a provocation or just entertainment? The article takes a closer look at the historical background and the content of the songs; it also questions the awareness of the criminal character of the SS displayed by the musicians. The time span covered by the songs in question reaches from the mid-1980s to the early 2000s. Thus, it can be asked if the attitude of musicians changed over time and if they included the current state of research in their lyrics.